Reflective Practice in Educational Research - Evans, Linda (Continuum, 2002)
Reflective practice in Educational Research' has established itself as a key recommended text on many postgraduate research methods courses in universities in the UK and abroad, including the Danish Pedagogic University and the University of Queensland. What this book offers is a collection of ideas and guidelines for developing more advanced skills in relation to specific selected qualitative research issues and, alongside these, discussion of these issues. It is a guide to developing as an educational researcher, written for those (students and academics alike) who have been introduced to basic research methods and wish to extend their repertoire of skills and increase their knowledge, competence and expertise, and incorporate more rigour into their work. Part I of the book, the Need for Improvement, contains two chapters that examine the problems within educational research and the rationale for making improvements. The much longer Part II focuses on ways of making such improvements. It contains eight chapters that examine specific qualitative research issues (including developing theory; categorising and classifying; and incorporating conceptual clarity and definitional precision) and ideas and guidelines for developing skills in relation to each
Keywords: méthodes de recherche; université; utilisation des recherches